PENGARUH PENGGUNAAN ELEVATION TRAINING MASK (ETM) TERHADAP PERUBAHAN NILAI VO2MAX, KAPASITAS VITAL PARU, DAN HEMOGLOBIN - Mila Ayu Hariyanti, - (2020)
ETM (Elevation Training Mask) constitute mask which are made to hinder breathing by making mechanism oxygen partial pressure reduce like at high altitude. The purpose of this study was to tes for influence utilization ETM against changes in value VO2Max, hemoglobin and lung vital capacity. This research method use quasi experiment, nonrandomized control group pretest-posttest design. Sample on this research is all over male softball athlete PON Banten U23. Measurement VO2Max, hemoglobin and lung vital capacity performed before and after intervention. Training programs begins with interval training (60 seconds Slow jog followed by 10 seconds Sprint with a distance 2 mile), Slow Continous Run ( Run with a distance 4 mile), and Circuit Training (Own Body Weight) 3 times a week. Utilization ETM arranged gradually with the height setting which increased during 6 weeks. Research results show that VO2Max score, hemoglobin and lung vital capacity has not changed much significant with exercises using ETM. Further research necessary by giving training modification in terms of duration, frequency and ETM usage time.